Pengaruh Karbon Monoksida Terhadap Lebar Bukaan Kaca Otomatis Replika Kabin Power window - Yuniarto Agus Winoko; Eka Febrianto (Universitas Merdeka Malang, 2026)
Cases of carbon monoxide (CO) poisoning inside vehicles continue to occur and often result in fatalities. This study aimed to investigate the relationship between CO gas concentration and the ventilation conditions of a cabin replica to determine the most effective power window opening width for minimizing the risk of poisoning, as well as to implement the system in a power window trainer. The research method involved designing and developing a power window trainer based on an Arduino Nano microcontroller. Experimental tests were conducted to quantitatively analyze the effects of variations in CO gas concentration and the number of ventilation openings, each with a diameter of 32 mm, on the automatic window opening width. The collected data were then analyzed using the Taguchi method. The results showed that higher CO gas concentrations resulted in wider window openings, with the maximum opening width reaching 5.8 cm at a CO concentration of 25 ppm. The number of ventilation openings also affected system performance, with the best condition achieved using one ventilation opening when the CO concentration reached 25 ppm. In addition, the fastest window-closing response was obtained when two ventilation openings were used at a CO concentration of 25 ppm